Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How would you compute this sum? It's not a problem I need to immediately solve, but a problem that came to my mind today. I think that the generalization to more than three nested sums would be interesting as well.

$$ \sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \sum_{p=1}^{\infty}\frac{(-1)^{m+n+p}}{m+n+p}$$

share|improve this question
    
By generalization, do you want $$\sum_{k_1,\dots,k_N=1}^{+\infty}\frac{(-1)^{\sum_{j=1}^Nk_j}}{\sum_{j=1}^Nk_j}‌​?$$ We can express the summand as an integral. –  Davide Giraudo Jul 25 '12 at 10:13
    
Can you show us, why you think that it converges at all? –  draks ... Jul 25 '12 at 10:31
    
Mathematica 8.0 is saying that the sum diverges. –  James Fennell Jul 25 '12 at 10:44
    
@Chris'sister can you show/link your WA? –  draks ... Jul 25 '12 at 10:49
    
@Chris'sister: in general it is better to use the MarkDown construction to post links. That is [link text](url to link to). I edited your comments above. This is one way to help prevent link breakage. –  Willie Wong Jul 25 '12 at 15:58

2 Answers 2

up vote 25 down vote accepted

Here is a simple lemma:

Let $(u_n)_{n\geqslant1}$ denote a decreasing sequence of positive functions defined on $(0,1)$, which converges pointwise to zero and such that $u_1$ is integrable on $(0,1)$. Then, $$ \sum\limits_{n=1}^{+\infty}(-1)^n\int_0^1u_n(s)\,\mathrm ds=\int_0^1u(s)\,\mathrm ds,\qquad u(s)=\sum\limits_{n=1}^{+\infty}(-1)^nu_n(s). $$

Now, let us consider the multiple series the OP is interested in. One sees readily that it does not converge absolutely hence the idea is to apply the lemma three times.

  • First, fix $n$ and $m$ and, for every $p\geqslant1$, consider $u_p(s)=s^{m+n+p-1}$. Then $u(s)=-\dfrac{s^{m+n}}{1+s}$ hence the lemma yields $$ \sum\limits_{p=1}^{+\infty}\frac{(-1)^{m+n+p}}{m+n+p}=(-1)^{m+n}\sum\limits_{p=1}^{+\infty}(-1)^{p}\int_0^1u_p(s)\,\mathrm ds=(-1)^{m+n+1}\int_0^1\frac{s^{m+n}}{1+s}\,\mathrm ds. $$
  • Second, fix $m$ and, for every $n\geqslant1$, consider $u_n(s)=\dfrac{s^{m+n}}{1+s}$. Then $u(s)=-\dfrac{s^{m+1}}{(1+s)^2}$ hence the lemma yields $$ \sum\limits_{n=1}^{+\infty}(-1)^{m+n+1}\int_0^1\frac{s^{m+n}}{1+s}\,\mathrm ds=(-1)^m\int_0^1\frac{s^{m+1}}{(1+s)^2}\,\mathrm ds $$
  • Third and finally, for every $m\geqslant1$, consider $u_m(s)=\dfrac{s^{m+1}}{(1+s)^2}$. Then $u(s)=-\dfrac{s^{2}}{(1+s)^3}$ hence the lemma yields $$ \sum\limits_{m=1}^{+\infty}(-1)^m\int_0^1\frac{s^{m+1}}{(1+s)^2}\,\mathrm ds=-\int_0^1\frac{s^{2}}{(1+s)^3}\,\mathrm ds. $$

Thus, the triple series the OP is interested in converges and the value $S_3$ of the sum is $$ \color{red}{S_3=-\int_0^1\frac{s^{2}}{(1+s)^3}\,\mathrm ds}=-\int_1^2\frac{s^{2}-2s+1}{s^3}\,\mathrm ds=-\left[\log(s)+\frac2s-\frac1{2s^2}\right]_1^2, $$ that is, $\color{red}{S_3=-\log(2)+\frac58}=-0.06814718\ldots$

The technique above shows more generally that, for every $k\geqslant1$, the analogous series over $k$ indices converges and that the value of its sum is $$ S_k=(-1)^k\int_0^1\frac{s^{k-1}}{(1+s)^k}\,\mathrm ds=(-1)^k\left(\log(2)+\sum_{i=1}^{k-1}(-1)^i{k-1\choose i}\frac1i(1-2^{-i})\right). $$

share|improve this answer
    
+1 Bravo! ${ }$ $ $ –  draks ... Jul 25 '12 at 11:56
1  
This is really, really nice. The $k=1$ case serves as another proof of the well-known alternating harmonic series sum,$$\sum_{k=1}^\infty \frac{(-1)^{k+1}}{k} = \log(2)$$ –  James Fennell Jul 25 '12 at 12:13
2  
In fact, the structure of the general answer is quite interesting: a transcendental constant plus purely algebraic terms. –  James Fennell Jul 25 '12 at 12:14
    
Chris' sister: The answer to this (where does this proof come from?) is in @James' remark: the method is an extension of a classical approach to prove that $S_1=-\log2$. –  Did Jul 25 '12 at 12:21

This didn' fit in a comment $$ \sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \left(\sum_{p=1}^{\infty}\frac{(-1)^{(m+n)+p}}{(m+n)+p}\pm(-1)^{m+n}\sum_{k=1}^{m+n}\frac{(-1)^{k}}{k}\right)\\ =\sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \left((-1)^{(m+n)}\sum_{p=1}^{\infty}\frac{(-1)^{p}}{(m+n)+p}\pm(-1)^{m+n}\sum_{k=1}^{m+n}\frac{(-1)^{k}}{k}\right)\\ =\sum_{m=1}^{\infty} \sum_{n=1}^{\infty}\left( \color{red}{ (-1)^{(m+n)}\sum_{p=1}^{\infty}\frac{(-1)^{p}}{(m+n)+p}+(-1)^{m+n}\sum_{k=1}^{m+n}\frac{(-1)^{k}}{k}}-(-1)^{m+n}\sum_{k=1}^{m+n}\frac{(-1)^{k}}{k}\right)\\ =\sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \left( \color{red}{ (-1)^{(m+n)}\sum_{p=1}^{\infty}\frac{(-1)^{p}}{p}}-(-1)^{m+n}\sum_{k=1}^{m+n}\frac{(-1)^{k}}{k}\right)\\ =\sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \color{red}{ (-1)^{(m+n)}\log(2)}-\Phi_{\text{Lerch}}(-1, 1, 1+n+m)+(-1)^{m+n}\log(2)\\ =\underbrace{\sum_{m=1}^{\infty} \sum_{n=1}^{\infty} (-1)^{(m+n)}2\log(2)}_{=0?}-\sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \Phi_{\text{Lerch}}(-1, 1, 1+n+m)\\ =-\sum_{m=1}^{\infty}\sum_{n=1}^{\infty} \Phi_{\text{Lerch}}(-1, 1, 1+n+m)\;, $$ and this is where I give up for now. W|A can do some examples, that make me believe, that this doesn't converge...

Ref's: $-(-1)^{m+n}\sum_{k=1}^{m+n}\frac{(-1)^{k}}{k}=-\Phi_{\text{Lerch}}(-1, 1, 1+n+m)+(-1)^{m+n}\log(2)$

share|improve this answer
    
Each inner sum of the double sum underlined with $=0?$ diverges hence the double sum diverges. –  Did Jul 25 '12 at 11:22
1  
@did And why don't they cancel infinitely often to $0$? –  draks ... Jul 25 '12 at 11:28
    
@did like Grandi's series... so let it be $0$ or $1$ or $1/2$. It would not affect to overall convergence/divergence... –  draks ... Jul 25 '12 at 11:41
    
Well, if you have no qualm about summing $\sum\limits_n(-1)^n$, what can I say... –  Did Jul 25 '12 at 11:54
    
@did maybe someting about: $\sum\limits_m\sum\limits_n (-1)^{m+n}=\sum\limits_m(-1)^{m}\sum\limits_n (-1)^{n}=\sum\limits_m(-1)^{m}G=G\sum\limits_m(-1)^{m}=G^2$, where $G$ is whatever you prefer as value for the Grandi series. So it converges, right? –  draks ... Jul 25 '12 at 12:04

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.